A God-Sized Vision: Revival Stories that Stretch and Stir. - Reeves, Russ P. (Fides et historia, 2012)
The article reviews the book ''A God-Sized Vision: Revival Stories that Stretch and Stir,'' by Collin Hansen and John Woodbridge.